Pinckney Fracture: do Not Underestimate Trauma of the Distal Phalanx of the Hallux - Nóbrega, J (2021)
Toe injuries are common in the emergency department and most of them are treated conservatively. In some circumstances, these injuries can present as a physeal fracture with concomitant soft-tissue injury affecting the nail bed and resulting in a hidden open fracture. To adequately treat these patients, a high index of suspicion is needed to diagnose and treat the open fractures and to prevent complications such as infection, osteomyelitis, malunion and premature physeal arrest.We report a case of a patient that was admitted to the hospital with a Salter-Harris type I fracture of the distal phalanx of the hallux. After confirming the diagnosis, antibiotic treatment was started and the fracture was reduced and fixed.The literature on this entity is sparse and most of the management protocols are based on its hand equivalent-the Seymour fracture, emphasising the low threshold for treating these lesions as an open fracture.